Managing Risk In Delta Ecosystems To Sustain Diverse Livelihoods - To Phuc Tuong (2009)
In the Mekong and the Ganges river deltas, saltwater intrusion when salt water from the sea moves up into the river poses problems for some farmers and opportunities for others. Salt water intrusion most often occurs during the dry season when river hydraulic pressure is low. For rice farmers in these regions saltwater intrusion threatens dry season rice crops that require fresh water, whereas shrimp farmers are able to expand the scale of their farming with the increase in brackish water during low-flow periods.